Enhancing MSMEs in Advancing High-Value Product Innovation - Ahhyuti Yu; Hantayi Whok; Ahtai See (Community Service Akseprin Journal, 2025)
Micro, Small, and Medium Enterprises (MSMEs) provide a crucial economic foundation in Indonesia, although they frequently encounter obstacles in creating products with substantial and lasting added value. Product innovation is essential for MSMEs to thrive in a progressively competitive global marketplace. This article examines techniques for empowering MSMEs to enhance high-value product creation. This project aims to identify the barriers to innovation encountered by MSMEs, develop effective mentorship models, and assess the effects of interventions on enhancing innovation capacity and producing high-value goods. The employed research methodology is a qualitative case study, incorporating in-depth interviews, participatory observations, and document analysis of MSMEs that have either innovated or are attempting to innovate. The study's results indicate that access to product design training, prototype development, the utilisation of basic technologies, and collaboration with specialists and research institutes can substantially motivate MSMEs to develop high-value goods. This article aids in the formulation of more focused empowerment policies and initiatives to promote sustainable innovation within the MSME sector